Social Capital and Innovation Policy in Croatia: Scientific Community as a Source of Innovation - Švarc, Jadranka; Šporer, Željka; Lažnjak, Jasminka (2009)
This paper provides the results of the first empirical research aimed at analyzing and understanding the influence of social capital on functioning and performing of innovation policy in Croatia. It is part of the wider project on social evaluation of the Croatian innovation policy and innovation system which is based on the survey conducted in 2007 and targeted at project leaders who have taken part in one of the first innovation policy programme in Croatia (HITRA-TEST programme). The programme was launched in 2001 with the aim to foster science-industry cooperation and commercialization of research results of the public research sector. It has provoked within the scientific community intensive debates concerning its efficiency, appropriate use of pubic money as well as ethical dilemmas about commodification of science that calls for shedding some lights on the innovation policy from the sociological point of view. The research starts from the presumption that project leaders within TEST programme, being the first in Croatia who applied for technology-oriented projects, are the agents of socio-cultural and institutional change that consists of the shift from the prevailing elite-type of science towards more productive use of the science. That can be identified with the shift from the standard science policy towards innovation policy. The investigation of their social characteristics (e.g. age, gender, institutional affiliation, area of research), attitudes towards commercialisation of science and entrepreneurial university and dimensions of social capital such as trust in institutions and value orientation provides a valuable picture of the group that responded to calls for collaboration with industry. It also gives an indication of the wider socio-cultural environment that shapes innovation policy implementation. The main hypothesis of the research is that motivation for application to TEST programme, as well as realisation of the project and satisfaction with achieved results is conditioned by: 1) set of variables of individual and scientific characteristics of the participants, 2) social capital defined as system of values and attitudes which regulate individual behaviour, attitudes toward commercialisation of knowledge, general value orientations and trust in the institutions. The four hypotheses were tested within this framework. The first hypothesis on dominantly scientific motivation for applying to TEST is confirmed. Second hypothesis that realisation of TEST projects has accomplished primarily scientific results also is confirmed while the third hypothesis that participants who have accomplished commercial results are more satisfied with the achieved results has not confirmed. Finally, the fourth hypothesis that performance of innovation policy is related to the deficit of social capital was confirmed due to findings on value structures of participants. The paper concludes that high presence of traditional values along with the attitudes toward commercialization of science illustrates the low capability of the Croatian society for institutional change and confirms the crucial role of social capital for successful implementation of innovation policy.
Projekt MZOS
Projekt MZOS
Projekt MZOS
ENG